PENILAIAN KINERJA GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM (Analisis Konseptual dan Implementatif) - Ahmad Aliyudin (Hijri, 2026)
Teachers have a primary task that has a huge influence on the progress of students and Madrasahs in education in Indonesia, so there needs to be an effort to improve the main duties and functions of teachers. Teacher Performance Assessment (PKG) is one effort in carrying out the duties and functions inherent in the functional position of teachers. This article uses a qualitative approach that discusses PKG from an Islamic perspective. Teacher performance assessment is important to evaluate the level of individual teacher performance in order to achieve maximum madrasah performance in accordance with Q.S At-Taubah: 105 as a form of world evaluation and supported in Q.S At-tin: 4 that humans are essentially obliged to learn throughout their lives.